Exports and Hedging Exchange Rate Risks: The Multi-Country Case - Axel F. A. Adam-Müller (University of Konstanz, Center of Finance and Econometrics (CoFE), 2000)
This paper examines the optimal production, export allocation and hedging decisions of a risk-averse international firm that exports to several foreign markets with different currencies. The firm faces multiple exchange rate risks. Optimal decisions are analyzed under two scenarios. In the first, there is a forward market for one currency only. Then, the export allocation to different markets is separable from the firm's preferences and the joint distribution of the exchange rates. In contrast, total production is not separable except for a special case. In the second scenario, there is a forward market for each currency. Then, both production and export allocation are separable. Hedging with forward contracts depends on risk premia and the joint distribution of the exchange rates. If tradable exchange rate risk is a linear function of untradable exchange rate risk plus noise, there is a conflict between cross hedging and taking a basis risk. If, alternatively, the untradable exchange rate risk is a linear function of the tradable exchange rate risk and noise, there is no such conflict. A speculative position in a biased forward market for one currency can be cross hedged using an unbiased forward market for another currency.
urn:nbn:de:bsz:352-opus-4489
Keywords: 330; Währungsmanagement; Außenhandelssektor; Export; Währungsrisiko; Hedging; Theorie